Identifying threats and opportunities for teleworking of both working couples during the corona outbreak - Saeed Taleshi, Leyla; Shafie Abadi, Abdollah; Yousefi, Emad (Journal of Adolescent and Youth Psychological Studies (JAYPS), 2023)
Background and Aim: As the lockdown or stay-at-home measures began, a large portion of the workforce was ordered to stay home and continue to work remotely. The purpose of the current research was to identify the threats and opportunities of remote work for both working couples during the outbreak of Corona. Methods: The present research method was qualitative using descriptive phenomenological method. The statistical population included teleworking couples, both employed, who had referred to counseling centers in Kerman. Among these, interviews were conducted with the couples using the available targeted sampling method, and the interviews continued until the theoretical saturation was reached. Qualitative data were collected using descriptive phenomenological method and semi-structured interview. Then the data was analyzed using the content analysis method. Results: The results of content analysis of data collected through in-depth semi-structured interviews showed that the lived experience of both working couples included two sub-themes of threats and opportunities. Conclusion: The sub-theme of opportunities is divided into the following categories: reducing wasted time, flexibility in allocating time, increasing planning ability, peace of mind due to the lack of direct supervision, cost savings, greater independence, stress reduction, and reduction of burnout and fatigue. The sub-theme of threats included the following categories: procrastination; Lack of focus on work; lack of focus on marital relationship; Social isolation; Ambiguity in responsibilities; Decreased motivation to work; reduction of work productivity; reducing the efficiency of group work; Ambiguity in roles; Ambiguity in the specific time of responsibilities; Decreased social bonding and perceived social support.